Edukasi Harga Konstan Rokok Djarum 76: Kajian Idealitas Psikologi Tasawuf Seorang Muslim - Robingun Suyud El Syam; A. Adibudin Al-Halim (Journal of Creative Student Research, 2023)
PT Djarum is a large cigarette company with a worldwide market share. It is interesting to study why one of Djarum 76's products can have a constant price under any circumstances. Through qualitative research with a phenomenological approach, the research shows: that the Djarum company is the producer of Djarum 76, it can achieve success because it is always consistent in its business so that it can lead its owner to become the richest person in Indonesia. Humans must cultivate the quality of their faith and piety consistently, then their life will be constant. God's help will come in a reciprocal relationship with the needs of a servant. Research implications, narrative experiences bring thought and faith to be consistent in life in various circumstances. Research is expected to contribute to the science of the psychology of Sufism